2010
DOI: 10.1037/a0017184
|View full text |Cite
|
Sign up to set email alerts
|

Only three factors of personality description are fully replicable across languages: A comparison of 14 trait taxonomies.

Abstract: We tested the hypothesis that only 3 factors of personality description are replicable across many different languages if they are independently derived by a psycholexical approach. Our test was based on 14 trait taxonomies from 12 different languages. Factors were compared at each level of factor extraction with solutions with 1 to 6 factors. The 294 factors in the comparisons were identified using sets of markers of the 6-factor model by correlating the marker scales with the factors. The factor structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
208
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 226 publications
(226 citation statements)
references
References 57 publications
13
208
1
1
Order By: Relevance
“…This approach is also exemplified by large-scale cross-cultural studies, which have WEIRD models, markers and instruments as a reference (e.g., Allik & McCrae, 2004;Bartram, De Fruyt, Bolle, McCrae, Terracciano, & Costa, 2009;De Raad et al, 2010;McCrae & Terracciano, 2005a, 2005bSchmitt et al, 2007;Zecca et al, 2012). These cross-cultural etic studies are based on tests of invariance or equivalence of measures that assess the multi-group comparability of constructs or scores (Byrne & Van de Vijver, 2014;Church et al, 2011).…”
Section: The Lexical Approach and Cross-cultural Psychologymentioning
confidence: 99%
See 4 more Smart Citations
“…This approach is also exemplified by large-scale cross-cultural studies, which have WEIRD models, markers and instruments as a reference (e.g., Allik & McCrae, 2004;Bartram, De Fruyt, Bolle, McCrae, Terracciano, & Costa, 2009;De Raad et al, 2010;McCrae & Terracciano, 2005a, 2005bSchmitt et al, 2007;Zecca et al, 2012). These cross-cultural etic studies are based on tests of invariance or equivalence of measures that assess the multi-group comparability of constructs or scores (Byrne & Van de Vijver, 2014;Church et al, 2011).…”
Section: The Lexical Approach and Cross-cultural Psychologymentioning
confidence: 99%
“…On the other hand, there are several studies that have failed to find evidence to prove the stability of the five factors and their facets between different cultures. For example, there are studies that found models with three (De Raad et al, 2010), six , seven , and nine factors , Daouk-Ory et al, 2016. In relation to this problem of cross-cultural replicability, De Raad et al (2010) concluded that they do not believe "that a final canonical response can be given, considering the incompatibility of specific language structures, each with different trait variables and different participants" (p. 171).…”
Section: The Lexical Approach and Cross-cultural Psychologymentioning
confidence: 99%
See 3 more Smart Citations